Paclobutrazol and Summer Pruning Influences Fruit Quality of Red Delicious Apple - Ashraf, N.; Ashraf, M.; Bhat, M. Y.; Sharma, M. K. (Indian Journal of Hill Farming, 2018)
Paclobutrazol and summer pruning can restrict vegetative growth and improve productivity and fruit quality in apple. The present experiment was carried out during two successive seasons on Red Delicious cultivar of apple. The study was carried out in arandomized block design with sixteen treatments and three replications. The trees were > 15 years old grown in experimental orchard of Division of Fruit Science, Sher-e-Kashmir University of Agricultural Sciences and Technology of Kashmir, Srinagar, Jammu and Kashmir, spaced at 5.49 Ã—5.49 metre distance. The study was aimed to show the effect of different concentrations of paclobutrazol along with different levels of pruning on fruitquality. With increase in paclobutrazol concentration and pruning levels, an increase in TSS, TSS/acid ratio, anthocyanin, sugars, fruit calcium and improvement in fruit grade was observed with decrease in fruit acidity.